Examing type and quality of preservice teachers’ lessons based on children’s literature - Ann Wheeler; Winifred Mallam (Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
This qualitiative research explores the types and levels of mathematical lesson tasks that 60 future elementary and middle school teachers created during an undergraduate mathematics content and pedagogy course. Data collection consisted of 51 children’s book inspired activities written by the preservice teachers. Using Stein et al.’s Task Analysis Guide as an assessment tool, the researchers coded the activities into 1 of 4 categories, as well as categorized each activity based on its mathematical content using the Common Core State Standards for Mathematics. Results showed that a majority of the PSTs wrote activities that were classified as Procedures with Connections. Also, a majority of the activities were geometry-based, specifically transformations and two-dimesional measurements. Implications for teaching include the fact that preservice elementary and middle school teachers can create mathematics lessons based on children’s literature, which often can include mathematical tasks that are making connections to procedural mathematics or even higher order thinking tasks.